Exploring E-learning Challenges During the Global COVID-19 Pandemic: A Review - Qurotul Aini; Mukti Budiarto; P. O. H. Putra; Untung Rahardja (Faculty of Computer Science Universitas Indonesia, 2020)
The world is currently battling the coronavirus disease 2019 (COVID-19) that has been declared as a global pandemic since mid-March 2020. The pandemic has inevitably impacted social and economic activities of the nation, including those in the education sector. As the governments have mandated universities to close their campuses, learning activities has been forced to move online. In this difficult situation, many university administrators, lecturers, as well as students may find it difficult to adapt to the so-called “new normal” ways of learning. Hence, as this is an unprecedented situation, this study explores the challenges faced by universities as academic institutions, lecturers, and students. This study starts by conducting a literature review concerning the challenges in e-learning in context of a pandemic. Data collected are then analyzed qualitatively using inductive thematic analysis technique, resulting in a taxonomy of e-learning challenges during a pandemic. Our analysis shows that students are challenged by connectivity, e-learning system support, and technological and self-regulation issues. On the other hand, lecturers are being challenged by competency, operational, self-regulation, and isolation issues. Meanwhile, institutions identify financial support and change management as challenging issues. This study highlights the need for further investigation to address the aforementioned challenges in e-learning.